Inovasi Interaktif Merancang dan Membangun Virtual Tour Asriloka Wonosalam Menggunakan Metode MDLC - Hendra Maulana; Tri Lathif Mardi Suryanto; Ronggo Alit; Wardhani, Lintang Sari Putri; Tsabita Safana Mustofa (Unversitas Muhammadiyah Riau, 2023)
Virtual tour (VT) technology is a virtualized digital technology that allows users to visit and explore locations without physically being there. This allows tourism owners to promote their tours using VT technology. One of them is Asriloka Wonosalam Ecotourism in Jombang, which is concerned with how potential visitors can see an overview of the facilities and atmosphere available. Through the Multimedia Development Life Cycle (MDLC) method, this paper aims to design and build Asriloka Wonosalam VT and then evaluate its application. This paper results in the design and creation of the Asriloka Wonosalam VT which has 3600 panoramic features, voice over information, text information, and a simple tour guide. The evaluation results show that 7 black box testing question items have a successful conclusion, finally the Asriloka Wonosalam VT was successfully created, implemented, and launched to support digital promotion.